DIPOLE-MODIFYING EFFECT OF STYRYLPYRIDINIUM DYES AND FLAVONOIDS ON THE MODEL MEMBRANES OF DIFFERENT LIPID COMPOSITIONS - Efimova, S S; Schagina, L V; Ostroumova, O S (T͡S︡itologii͡a, 2017)
The changes in the dipole potential of lipid bilayers (jd) mimicking cell membranes induced by the adsorption of low molecular weight amphiphiles, flavonoids (phloretin and quercetin) and styrylpyridinium dyes (RH 421 and RH 237) were measured. The method based on the determination of ionophore-induced transmembrane current was used to evaluate the changes in jd after the addition of the modifiers. The characteristic parameters of the Langmuir adsorption isotherm, the maximum changes in jd at an infinitely large concentration of flavonoid and its desorption constant, which reflects the affinity of the flavonoid to the lipid phase, were determined. The slopes of linear dependencies of increasing in jd on the concentration of the styrylpiridinium dyes in membrane bathing solution were defined. It was found that the dipole-modifying effect of phloretin depends on the charge of the lipids forming the membranes, while the ability of quercetin to reduce jd turned on the initial hydration of the bilayers. The results indicated on the different mechanisms of the decrease in jd at the adsorption of tested flavonoids. It was shown that the changes in jd at the incorporation of styrylpyridinium dyes into bilayers is determined by the interaction of the modifiers with the membrane components.